EVALUASI PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PERUSAHAAN KONSTRUKSI - Ira Riswana; Susilawati (CV. ADIBA AISHA AMIRA, 2022)
Occupational safety and health is important not only in companies but everywhere, such as educational institutions, construction sector and companies. This obligation regarding the implementation of the K3 Management System by each company is regulated in PP No. 50 of 2012 concerning the Implementation of the Occupational Health and Safety Management System. This research is a literature review, where the data sources in this study come from several published journals obtained from the search engine